2010
DOI: 10.1037/a0019460
|View full text |Cite
|
Sign up to set email alerts
|

A comparative view of face perception.

Abstract: Face perception serves as the basis for much of human social exchange. Diverse information can be extracted about an individual from a single glance at their face, including their identity, emotional state, and direction of attention. Neuropsychological and fMRI experiments reveal a complex network of specialized areas in the human brain supporting these face-reading skills. Here we consider the evolutionary roots of human face perception by exploring the manner in which different animal species view and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(210 citation statements)
references
References 312 publications
3
191
0
1
Order By: Relevance
“…First, OT may make gaze more determined by perceptual features of the stimulus and less responsive to the goals of the animal. The eye region is a high contrast area (28) and contrast is an image feature which normally attracts gaze during image viewing (29). OT may increase the impact of this stimulus feature on gaze (30), perhaps through down-regulating goal-directed social attention and species-typical social vigilance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, OT may make gaze more determined by perceptual features of the stimulus and less responsive to the goals of the animal. The eye region is a high contrast area (28) and contrast is an image feature which normally attracts gaze during image viewing (29). OT may increase the impact of this stimulus feature on gaze (30), perhaps through down-regulating goal-directed social attention and species-typical social vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the gaze effects reported here and the decision making effects reported previously in this species (4) are strikingly similar to previously reported findings in humans. Like humans, the rhesus macaque is a group-living primate that uses visual displays to communicate and guide social behavior (28).…”
Section: Discussionmentioning
confidence: 99%
“…Craniofacial anomalies are a diverse set of congenital and acquired conditions with a significant individual and societal burden; they are associated with a high incidence of speech, hearing, oral function, appearance, and social morbidity (Leopold & Rhodes, 2010;Mosey, 2004). The treatment of CFA, preferably monitored in a non-invasive manner, can ameliorate this morbidity.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Second, social complexity is a critical factor in shaping species intelligence and encephalization (Humphrey, 1976;Shultz & Dunbar, 2010). Third, behavioral and ethological testing has shown that socially oriented species across a range of taxa are capable of monitoring and interpreting the behaviors of their conspecifics (Byrne & Bates, 2010;Leopold & Rhodes, 2010). Thus there is good reason to believe that high-level social perception is common in the animal world, that its level of expression varies widely among species, and that it has coevolved with measurable changes in the brain.…”
Section: * * *mentioning
confidence: 99%